1989
DOI: 10.1080/00288306.1989.10425715
|View full text |Cite
|
Sign up to set email alerts
|

Late Pliocene distal silicic ignimbrites, Port Waikato, New Zealand: Implications for volcanism, tectonics, and sea-level changes in South Auckland

Abstract: At least five distal silicic ignimbrites occur in coastal alluvial plain pumiceous sandstone, mudstone, and peat of the basal Kaihu Group at Oruarangi, 5 Ian south of Port Waikato on the southwest Auckland coastline. The ignimbrites are 0.1-3.0 m thick, include rip-up paleosol clasts, carbonised logs, and gas-escape pipes, and are intimately associated with synignimbrite sedimentary wash deposits. The ignimbrite-bearing succession rests on Jurassic Huriwai Group and is unconformably overlain by thick dune-sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although the pyroclastic flow described by Wilson et al (1995) covers most of the Auckland Region, it was suggested by the same authors and by Nelson et al (1989) that topographic barriers south of Auckland, formed since 1 m.y. B.P., will prevent future pyroclastic flows inundating the Region to their previous extent.…”
Section: Hazard Extentsmentioning
confidence: 92%
See 3 more Smart Citations
“…Although the pyroclastic flow described by Wilson et al (1995) covers most of the Auckland Region, it was suggested by the same authors and by Nelson et al (1989) that topographic barriers south of Auckland, formed since 1 m.y. B.P., will prevent future pyroclastic flows inundating the Region to their previous extent.…”
Section: Hazard Extentsmentioning
confidence: 92%
“…In extreme cases it is possible that pyroclastic flows and co-ignimbrite ash may also reach the Region (Nelson et al 1989;Wilson et al 1995). Other potential hazards include poisonous gases and acid rain, mudflows and mudfills, flooding, climate variations and possibly earthquakes.…”
Section: Volcanic Hazardsmentioning
confidence: 96%
See 2 more Smart Citations